Environmental change induced by water engineering development dominates the global watershed sustainable development issues - Meng, Zhu; Cheng-Qi, Zhang; Qi, Feng; Ju-Tao, Zhang; Wei, Liu; Ling-Ge, Wang; Yuan-Yuan, Xue; Ying-Qing, Su (Frontiers in Environmental Science, 2024)
Global watershed sustainable development has experienced world-wide threats from continuing anthropogenic stressors, and the need to deepen and broaden research encompassing the intersection in global environmental change as well as environmentally oriented watershed sustainable development (EOWSD) has been noticed. However, there is not yet a widely recognized cognition on the applicability and scope of various EOWSD issues, and the zoning of global EOWSD issues is remains uncertain despite it is crucial for achieving global watershed sustainable development. This research was conducted to both clarify the zoning and evolution of various EOWSD issues around the world, and differentiate the relative impacts on EOWSD of climate change and human activities. The global EOWSD issues were summarized from 62 watersheds around the world as 6 categories associated with different aspects of global watershed sustainability. And the partition method, in which the spatial and temporal variations of global summer Normalized Difference Vegetation Index in summer were examined and the quantitative climate classification were conducted, indicates a clear and definite relationship between the zoning of EOWSD issues and 8 natural geographical zones. Meanwhile, we selected 34 watersheds either or both are the 100 most populous river basins and the 100 largest (by area) river basins in the world from the 62 watersheds to assess relative effects of human impact on watershed sustainability. Results from the numerical analyses of baseline water stress (BWS) values, which was used to provide a robust measure of human impact and evaluate the impact and relative importance of human-induced changes on watershed sustainability, indicate that the human activities do not affect the zoning of EOWSD issues at global scale while the environmental change induced by water engineering development should be certain to affect that on the long-term. Our findings present a new perspective to illustrate the relationship among global EOWSD, environmental change and human impacts, and will also provide a scientific basis on setting future emphasizes of global watershed sustainable development and furthering the related disciplines.